2013
DOI: 10.1016/j.chb.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simultaneously observing and making gestures while studying grammar animations on cognitive load and learning

Abstract: This study examined whether simultaneously observing and making gestures while studying animations would lighten cognitive load and facilitate the acquisition of grammatical rules. In contrast to our hypothesis, results showed that children in the gesturing condition performed worse on the posttest than children in the non-gesturing, control condition. A more detailed analysis of the data revealed an expertise reversal effect, indicating that this negative effect on posttest performance materialized for childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 34 publications
3
35
1
Order By: Relevance
“…Future research could use a delayed test to determine the long-term effects of learning math by mirrorbased observation of one's own movements. Another recent study by Post et al (2013), similar to this study in the aspect of using a combination of observation and making movements (i.e., gesturing) in grammar learning, is consistent with the null results. In this study, children were instructed to simultaneously gesture along with the instruction gestures (i.e., imitation) in the animation.…”
Section: Discussionsupporting
confidence: 78%
“…Future research could use a delayed test to determine the long-term effects of learning math by mirrorbased observation of one's own movements. Another recent study by Post et al (2013), similar to this study in the aspect of using a combination of observation and making movements (i.e., gesturing) in grammar learning, is consistent with the null results. In this study, children were instructed to simultaneously gesture along with the instruction gestures (i.e., imitation) in the animation.…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, recent research has suggested that when learning higher level aspects of an L2 (semantics and syntax), observing (Kelly & Lee, 2012) and producing (Post, Van Gog, Paas, & Zwaan, 2013) gestures help only when cognitive demands are low. The SO group made significant improvement on all four item categories (the word-initial and word-final vowels at the slow and fast rates), whereas the other groups improved in only three of the four categories.…”
Section: Discussionmentioning
confidence: 99%
“…However, Goldstone and Sakamoto (2003) offered different conclusions; they found that students with higher ability were positively affected 168 by concrete and clearly pictorial materials, and an opposite effect was found for students with lower ability. Recently, Post, Van Gog, Paas, and Zwaan (2013) also found that asking students with lower language ability to simultaneously observe and make gestures did not lighten cognitive load and facilitate the acquisition of grammatical rules as expected. Contrarily, the gesturing group had a worse performance than the non-gesturing group.…”
Section: Limitations Of the Present Study And Suggestions For Future mentioning
confidence: 99%